The Capital Requirements (Basel III) and the Banking Sector Business Activity - Larionova, I.V.; Meshkova, E.I.; Zubkova, S.V. (Journal of Reviews on Global Economics, 2018)
Active development by international organizations and national regulators of the emergent standards purporting prevention of crises and increase of banking stability is typical for the last years. However, practical implementation of the standards is not so definitive. This article is devoted to the analysis of impact of new requirements in the field of control over the quality and adequacy of the capital of banks, introduction of the additional parameters of risk-related load on the basis of financial leverage on business activity of banking sector. The issue of correlational study of capital adequacy ratio of banks and their credit activity was considered by different scientists over the last years; however, no decisive results were obtained. At the same time, the belief on the change of capital requirements and bank loans prevails. Generally, after strengthening of capital requirements, the banks reduce the loan growth. The authors of research prove this conclusion for the Russian economy. Following carried out analysis, the conclusion was also drawn that against the background of essential excess of the planned level of financial leverage, banks generated a highly risky asset portfolio, where the new standard did not address. It is the authors’ opinion that for the purpose of impact on financial activity, the leverage levels must be differential for banks having various business models.